Code Switching used by Maudy Ayunda in Najwa Shihab YouTube Channel - Wayan Widia Sri Meniang; Ni Luh Nyoman Seri Malini; Made Detriasmita Saientisna; I Made Suastra (Jurnal Langua, 2023)
This study was focused on an analysis of code-switching used by Maudy Ayunda found in the youtube video Catatan Najwa bersama Maudy Ayunda, which was hosted by Najwa Shihab. This study aimed to identify the types of code-switching and to know the reason for using code-switching by Maudy Ayunda. This research was classified as qualitative research with a descriptive method. The data of this study were collected by watching the video on Najwa Shihab's youtube channel and then analyzed descriptively. The theory used to analyze the types of code-switching is the code-switching theory by Hoffman (1991). According to Hoffman (1991), there are four types of code-switching: intra-sentential switching, inter-sentential switching, emblematic and establishing continuity. The code-switching theory by Hoffman (1991) was also used to describe the reason for using code-switching. Hoffman (1991: 116) classified the reasons to use code-switching into seven points, namely, talking about a particular topic, quoting somebody else, being emphatic about something, interjection, repetition used for clarification, intention of clarifying the speech content for the interlocutor and expressing group identity. As a result, in the conversation duration of 26 minutes, it was found that Maudy used the most inter-sentential switching, and the reason was talking about a particular topic.